The Principles of Fairness and Togetherness in the Land Distribution in Sapuro Religious Tourism - Azmi, Ulul; Werdi, Oktaviana Lalita; Hidayatullah, Ahmad; Bhakti, Wirayudha Pramana; Fasya, Adib ‘ Aunillah (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2023)
Religious tourism is a form of travel activity to a special place that is related to the religious field. This activity has its own meaning for every member of a particular religion. The purpose of this study is to explain and describe the principles of fairness and togetherness in the division of land at the religious tourism object of Sapuro. The study used a qualitative descriptive method. It is research by describing and interpreting the meaning of data that has been collected through the stages of observation and interviews. This information is in the form of a brief biography about the Sapuro Tomb, the principles of fairness in the distribution of land at the Sapuro religious tourism object, as well as the principle of togetherness in the distribution of land at the Sapuro religious tourism object. The principle of fairness in the distribution of land in Sapuro Tomb religious tourism is carried out by taking a number to get the land for sale. It has been approved by the traders and this method is considered fair. The principle of togetherness in the distribution of land in Sapuro religious tourism is seen in how local traders of the Sapuro village happily accept traders who are from outside the Sapuro village.